Use of salivary biomarkers for diagnosis of periodontal disease activity: a literature review - Rocha, Fernanda Regina Godoy [UNESP]; Molon, Rafael Scaf de [UNESP]; Tonetto, Mateus Rodrigues [UNESP]; Pinto, Shelon Cristina Souza; Muñoz, Eduardo Mariscal [UNESP]; Sampaio, Jose Eduardo Cezar [UNESP] (Jaypee Brothers Medical Publishing, 2013)
Periodontal disease is an infectious disease characterized by the connective tissue destruction and consequent alveolar bone loss in response to plaque accumulation on the tooth surface. The clinical diagnosis of periodontal disease is based both on clinical examination involving the evaluation of probing depth and radiographic examination of alveolar bone loss but these examinations are not enough to determine the activity of the disease process. For that reason, it has been proposed to seek predictive disease markers in an attempt to assess the disease activity and so, evaluate the efficacy of the periodontal disease treatment. The aim of this review is to present recent advances in the development of proteomic, genomics and microbial biomarkers and potential clinical applications. It was concluded that periodontal treatment based on assessing the levels of salivary biomarkers emerges as a promising method in near future and will become an integral part of the evaluation of periodontal health.
Keywords: Salivary glands; Periodontal disease; Oral diagnosis; Periodontitis